Highly selective and sensitive response of Polypyrrole–MnO2 based composites towards ammonia gas. Issue 4 (20th May 2018) - Malook, Khan; Khan, Hamayun; Shah, Mutabar; Haque, Ihsan‐Ul‐
Abstract : Polypyrrole (PPy) and PPy/MnO2 composites of varying wt% of MnO2 were synthesized by chemical oxidation polymerization. The synthesis of the required samples was confirmed by Fourier transform infrared spectroscopic studies. The PPy was amorphous and all its composites with MnO2 were of crystalline nature as confirmed by x‐ray diffraction analyses. The PPy was of globular morphology while the composites were of elongated shape maintaining the morphology of MnO2 as ratified by scanning electron microscopy. The actual relative amount of MnO2 in the composites was greater than the amount added. The gas sensitivity and selectivity of the samples was checked for ammonia gas and some organic liquid vapors using LCR (L = inductance, C = capacitance, R = resistance) meter as resistance detector. The effect of MnO2 amount in the composites, concentration of ammonia and working temperature was studied on sensitivity of the materials. The composite with 10 wt% of MnO2 was found to be of the best performance having working range of 1–30 ppm and limit of detection 0.4 ppm. Similarly, this material showed excellent dynamic response, sensitivity and selectivity towards ammonia gas with response and recovery time of 32 and 40 s respectively. POLYM. COMPOS., 40:1676–1683, 2019. © 2018 Society of Plastics Engineers